GitHub: exploring the space between boss-less and hierarchical forms of organizing - Richard M. Burton; Dorthe Døjbak Håkonsson; Jackson A. Nickerson; Phanish Puranam; Maciej Workiewicz; Todd R. Zenger (Journal of Organization Design, 2017)
In this edition of the organizational zoo series, we take a closer look at an interesting organization design case-GitHub, a software company from California. Similar to Valve, the subject of the previous article in the series (Puranam and Håkonsson, J Organ Design 4: 2-4, 2015) GitHub is used to delegate the choice of projects and project allocation to its workers, fitting the recent trend in running organizations without bosses. The interesting fact about GitHub is that after years of praising its own unorthodox organizational structure, the company suddenly decided to abandon it for something much more traditional. We asked several renowned organization scientists to share their thoughts on this interesting case and discuss what we can learn from it.
Keywords: 650; New forms of organizing; Organizational design; Boss-less organization; Self-allocation; Organizational change